Development of terrain height multipliers and roughness lengths for Seberang Perai reogion - Norhaiza, Ghazali (2010)
Malaysia has developed its own standard of practice in wind loading known as MS 1553:2002 Code of Practice on Wind Loading for Building Structure. During the development of this Malaysian Standard, reference was made to Australian Standard due to the similarity of wind climate between Malaysia and Australia. In the same time, researches have been carried out in order to update all parameters in MS 1553:2002 based on Malaysia wind climate. Seberang Jaya Telecommunication Tower was selected as the study area representing terrain Category 3: Suburban area for Seberang Perai region. An eight years period of data are recorded at three different levels by using the Ultrasonic Wind Sensor (UWS). Power Law profile is the best equation fit with the vertical wind speed profile at the study area as proven by Ramli (2005). In this study, Terrain Height Multiplier, Mz,cat, and Roughness Length, z0 for all terrain categories in Seberang Perai region are defined by using statistical and mathematical method. From the results obtained, the proposed M4cat for all terrain categories are much lower than the current values in MS 1553:2002. The difference up to 19% obtained due to the fact that Australia and Malaysia have different wind climate. A reasonable good agreement and a consistent result for Mz,cat can be noted from the comparison of the proposed value to the other international codes and standards. The proposed z0 for all terrain categories are in range from 0.03 m to 1.13 m which is still in the overall range for all codes and standards.